2018
DOI: 10.1007/s40262-018-0661-6
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically-Based Pharmacokinetic Model to Describe Ciprofloxacin Pharmacokinetics Over the Entire Span of Life

Abstract: BackgroundPhysiologically-based pharmacokinetic (PBPK) modeling has received growing interest as a useful tool for the assessment of drug pharmacokinetics by continuous knowledge integration.ObjectiveThe objective of this study was to build a ciprofloxacin PBPK model for intravenous and oral dosing based on a comprehensive literature review, and evaluate the predictive performance towards pediatric and geriatric patients.MethodsThe aim of this report was to establish confidence in simulations of the ciprofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 108 publications
1
28
0
Order By: Relevance
“…To date, a few studies have been conducted on PBPK models to predict drug concentration in the geriatric population. In these models, alterations of certain physiological parameters with aging were considered, such as alveolar ventilation, cardiac output, different organs (e.g., liver, brain, heart, kidney, spleen, left and right lung) weights, and blood flows [9][10][11][12][13]. However, most models were developed in the Caucasian geriatric population whose physiological variables and PK characteristics were not necessarily same as Chinese geriatric population.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few studies have been conducted on PBPK models to predict drug concentration in the geriatric population. In these models, alterations of certain physiological parameters with aging were considered, such as alveolar ventilation, cardiac output, different organs (e.g., liver, brain, heart, kidney, spleen, left and right lung) weights, and blood flows [9][10][11][12][13]. However, most models were developed in the Caucasian geriatric population whose physiological variables and PK characteristics were not necessarily same as Chinese geriatric population.…”
Section: Introductionmentioning
confidence: 99%
“…= intrinsic clearance (µL/min/mg protein). 1 as per PK-Sim ® library value if not indicated otherwise, 2 as reported in Schlender et al, 2018 [ 29 ] if not indicated otherwise, 3 optimized, 4 Carver et al, 1989 [ 27 ], 5 Charman et al, 2020 [ 47 ], 6 ChemAxon ( ), 7 Kotila et al, 2013 [ 42 ], 8 solubility in mg/mL at indicated pH (@ pH), 9 ALOGPS 2.1 ( ), 10 B:P optimized via V f.proteins = 0.19 and V f.lipid = 0 in blood cell, 11 B:P optimized via V f.proteins = 0.06 and V f.lipid = 0 in blood cell, 12 calculated in PK-Sim ® , 13 Absorption modification Enhancement factors for Cecum = 26.24 and other regions of large intestines = 0.…”
Section: Resultsmentioning
confidence: 99%
“…The ciprofloxacin PBPK model used in this study was adapted from a previously published model [ 29 ]. Some model refinements were performed to match the clinical plasma concentrations in healthy American adult volunteers ( n = 14) after a 750-mg oral dose [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…A value of 5.24×10 −6 cm/min was used in this model after the parameter identification feature of the modeling program. 37 The specific intestinal permeability of propranolol reported in the literature ranged from 2.8×10 −4 -6.67×10 −4 and 6.67 ± 3.42 ×10 −4 cm/s. 38,39…”
Section: Absorptionmentioning
confidence: 95%